Ships, Shells, and Sanctions: The EU’s Fight Against Trade-Based Sanctions Evasion - A legal analysis of trade misrepresentation techniques and the role of private sector actors in the enforcement of EU restrictive measures - Puchkova,Angelina; Jablonska,Oliwia Krystyna (2025)
This research investigates the legal framework of the European Union (EU) in addressing trade-based sanctions evasion, with a specific focus on the role of private sector actors, specifically financial institutions and shipping companies. Trade misrepresentation — a rising method for moving illicit funds through techniques such as under-invoicing, over-invoicing, phantom shipments, complex corporate structures and more — is a challenge to enforcing EU restrictive measures. With the enforcement delegated to Member States and further private actors, sanctioned entities attempt to mask their activities with legitimate commercial flows, exploiting legal loopholes. Findings reveal a significant asymmetry in obligations for private entities: financial institutions face well-defined obligations, while the logistics sector operates under vague and fragmented guidance. Limited data access, transparency and self-reporting issues further undermine the detection of effective sanctions evasion. Despite regulatory progress, the current framework remains underdeveloped to effectively detect sanctions evasion via trade misrepresentation techniques.
Keywords: EU sanctions; trade-based sanctions evasion; private sector compliance; trade misrepresentation; financial institutions; shipping companies; anti-money laundering; beneficial ownership